(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless networks have certainly been a revolution in today’s technologically as one of the most vital and active fields in the communication industries. These wireless ad-hoc networks consists of independent nodes with decentralized administration and physical infrastructures, with a dynamic topology in which nodes can easily leave or join the network at all time and also move freely. In other not to compromise the confidentiality, and integrity of network services, the safety of packets data can only be achieved by guaranteeing that the problem of security has met the requisite standard. The performance analyses of routing protocols for Ad-Hoc wireless networks, DSDV, DSR and AODV were investigated using network parameters such as averages throughput, packet delivery ratio and End-to-end delay using various scenarios of mobile node and size of the network. Awk script was used to analyze the trace file and produce the average throughput, packet delivery ratio and end-to-end delay as the result of the simulation. The simulation was run by implementing codes in DSDV, DSR and AODV CC class files to accommodate the behavioral pattern of attacks. The results analysis of routing protocols under the security attacks, it was observed that the DSDV significantly has lower performance as a result of frequent link changes and connection failures which led to heavy overload and congestion problems. Furthermore, when comparing the two reactive routing protocols, AODV performs better than DSR.